Dynamics of Control and Resistance: Reactions to the Modern Policy of Assimilation of the Travellers in Norway - Halvorsen, Rune (Nordlit, 2004)
For much of the 20th century, the Norwegian authorities pursued a strict assimilation policy towards Travellers (tatere/ romanifolket) and their culture. As was the case in many other countries, Travellers were constructed as "the other" (Riggins 1997, MacLaughlin 1999). When compared to other Western European countries, it is, however, surprising that Norwegian Travellers were seen as such a serious problem and threat during the 20th century. The 1845 census counted 1145 Travellers out of a total population of 1.3 million in Norway (Sundt 1852, SSB 1968: Table 13). A private charity organisation acting on behalf of the state registered 5129 "itinerants" in their archives from 1900 to 1959 (Haave 2000). These were the figures that worried the elites. This paper examines the modern assimilation policy and Travellers’ reactions to this policy. In particular the paper analyses the internal relation between the modern assimilation policy and the emergence of collective demands for recognition as an ethnic minority and moral redress among Travellers in the 1990s.